Adoption of Distance Education and Mobile Technology by University Students - Orazbekovna, Seidaliyeva Gulnara; Orazbekovna, Seidaliyeva Gaukhar; Ydyrysbayev, Darkhan; Zhakypbekova, Gulnar; Sydykhov, Bakhyt (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The aim of this study is to determine the adoption of distance education and mobile technology by university students. Quantitative research method was used in the study. The research was conducted in the fall semester of 2021-2022. Volunteer 412 university students continuing their education in Kazakhstan participated in the research. In the research, 3-week online education mobile technology training was given to university students. "Mobile Technology in Education" measurement tool developed by the researchers and compiled by experts in the field was used in the research. The measurement tool was delivered and collected by university students via online method. The analysis of the data was made by using the SPSS program, frequency analysis, t-test, and the results were added to the research in the presence of tables. According to the results obtained from the research, it was concluded that there was a significant difference between the post-test mobile technology status of university students and that their mobile technology status was high.